Effects of cervical conisation on pregnancy outcome: a meta-analysis - Zhuang, Hongmei; Hong, Shurong; Zheng, Lin; Zhang, Layue; Zhuang, Xueyi; Wei, Hua; Yang, Yuqing (Journal of obstetrics and gynaecology, 2019)
To assess the effect of cervical conisation on pregnancy outcome, a literature search strategy was conducted to identify all of the references lists of the relevant studies. The fixed or random effect model was used to calculate pooled RRs on the basis of heterogeneity. Twenty-seven publications with n cases and m controls were included in the meta-analysis. The results showed that conisation was associated with a higher risk of a preterm delivery (p = .010), PROM (p = .008), and a lower birth weight (p < .001) in overall effect. The subgroup analysis showed that CKC was associated with a significantly increased risk of a preterm delivery (p < .001), and a lower birth weight (p< .001). LLETZ was associated with preterm delivery (p = .004) and a lower birth weight (p = .020). The results suggested that cervical conisation increases the risk of a preterm delivery, PROM, and a lower birth weight, especially in a CKC and LLEETZ procedure. Impact statement What is already known on this subject? Currently, the three main excisional procedures for cervical intraepithelial neoplasia (CIN) treatment are laser conisation, cold-knife conisation (CKC), and a large loop excision of the transformation zone (LLETZ). CKC and LEEP/LLETZ were significantly associated with a preterm delivery and low birth weight, and that former was associated with higher relative risks than the latter one. What do the results of this study add? The present results showed that conisation was associated with a higher risk of a preterm delivery, PROM, and a lower birth weight in overall effect. A subgroup analysis showed that CKC was associated with a significantly increased risk of a preterm delivery, and a lower birth weight. LLETZ was associated with a preterm delivery and lower birth weight. What are the implications of these findings for clinical practice and/or further research? This study is of clinical significance by showing that cervical conisation increases the risk of preterm delivery, PROM, and a lower birth weight, especially in a CKC and a LLEETZ procedure.